Defining Patient Safety Events in Inpatient Psychiatry. Issue 8 (December 2021) - Marcus, Steven C.; Hermann, Richard C.; Cullen, Sara Wiesel
Abstract : Objectives: The past 20 years have seen the emergence of a national movement to improve hospital-based healthcare safety in the United States. However, much of the foundational work and subsequent research have neglected inpatient psychiatry. The aim of this article was to advance a comprehensive approach for conceptualizing patient safety in inpatient psychiatry as framed by an application of the Institute of Medicine patient safety framework. Methods: This article develops a framework for characterizing patient safety in hospital-based mental health care. We discuss some of the conceptual and methodological issues related to defining what constitutes a patient safety event in inpatient psychiatry and then enumerate a comprehensive set of definitions of the types of safety events that occur in this setting. Results: Patient safety events in inpatient psychiatry are broadly categorized as adverse events and medical errors. Adverse events are composed of adverse drug events and nondrug adverse events, including self-harm or injury to self, assault, sexual contact, patient falls, and other injuries. Medical errors include medication errors and nonmedication errors, such as elopement and contraband. We have developed clear definitions that would be appropriate for use in epidemiological studies of inpatient mental health treatment. Conclusions: Psychiatry has not been an integral part of the national safety movement. As a first step toward breaching this chasm, we have considered how psychiatric events fit into the safety framework adopted across much of medicine. Patient safety should become a key part of inpatient psychiatry's mission and pursued rigorously as the subject of research and intervention efforts.